A microcantilever investigation of size effect, solid-solution strengthening and second-phase strengthening for < a > prism slip in alpha-Ti - Gong, J; Wilkinson, A (2011)
Microcantilevers of various sizes were machined using a focused ion beam from commercially pure (CP) Ti, Ti-6Al and Ti-6Al-4V, and tested in bending using a nanoindentor in order to study the size effect, solution strengthening and second-phase strengthening in α-Ti. Slip on the 〈a〉 prismatic system was activated by selecting the crystal orientation of α-phase in the cantilevers. The critical resolved shear stresses (CRSSs) were determined via an inverse process of fitting a crystal plasticity finite element model to the experimental load-displacement data. Cantilevers had an equilateral triangular cross-section and cantilevers with widths w of 10, 5, 2 and 1 μm were tested. For each material the increase in CRSS τ with reducing cantilever width w is represented well by the expression τ= τ0+Aw, where τ 0 is the CRSS for an infinite sample and A is a constant. Such a variation of CRSS with beam size is well accounted for by the increased back stress generated by dislocations piling up at the neutral axis. The CRSS values extrapolated to infinite sample size are 86 MPa for the CP-Ti, 308 MPa for the Ti-6Al and 444 MPa for the 〈a 3〉 slip in the Ti-6Al-4V. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.